A new scalable-up approach to non-iridescent structural blue films with relatively high tensile properties via RAFT emulsion polymerization. (5th December 2016) - Xiang, Qing; Luo, Yingwu
Abstract: A new scalable-up approach to the nanostructured films with high quality non-iridescent blue color was demonstrated by cast of soft shell/hard core latex spheres synthesized via RAFT emulsion polymerization. A series of PnBA soft shell/PSt hard core latex nanospheres with different core/shell structures were synthesized via RAFT emulsion polymerization. In contrast to conventional colloidal photonic crystals, the nanostructured films possessed relatively high tensile mechanical properties resulting from the dense structures and non-iridescent structural blue color because of random phase structures. It was found that the color quality of the nanostructured films was highly dependent on the size, shape and separation degree of the dispersed phase. Unexpectedly, the irregular-shape dispersed phase around 120 nm in size and sharp phase interface were found to significantly improve the quality of blue color. When films are too thick (>0.25 mm), the color saturation would be affected, which could be partly eliminated by adding carbon black. Graphical abstract: Highlights: A simple and facile method to fabricate films with structural blue color is proposed. Well-defined core/shell particles are synthesized via RAFT emulsion polymerization. Color quality is affected by size, shape and separation degree of the dispersed phase. The films show relatively high tensile properties. The method is scalable-up to fabricate large-scale films.